Impact of the Ontario Works program on the quality of life of Aboriginal people living on reserve in Northern Ontario / by Janis Yahn. - Yahn, Janis (2009)
An important goal for many First Nations communities is to increase the economic health and development of their community by assisting community members to become employable through education and training programs as well as providing opportunities for employment. The present study was undertaken to evaluate the impact of the Ontario Works program, a provincially funded income and employment assistance program, on the quality of life of Aboriginal people living on reserve in Northern Ontario. The study also looked at those who have experienced the shift from social assistance to employment to assess the extent to which participation in the program affected economic status and overall sense of health and well-being. Fifty-nine Ontario Works clients from Wikwemikong were interviewed on quality of service and impact of the program. Eleven employers were also interviewed on the challenges facing Ontario Works clients and opportunities to address the challenges. The interviews revealed six major themes: 1) social assistance is used primarily by females and single parent families, 2) income assistance is not enough to support a family with children, 3) Ontario Works has increased the overall health and well-being of participants, 4) participation in employment support programs has increased employability, 5) higher education increased the opportunity to secure long term employment, and 6) employment stabilizes families and increases quality of life. A focus group session was held in the community to validate the data and provide feedback on the results of the study. The findings identified several positive aspects of the program that were presented as ‘best practices’. There were also a number of limitations in the services that were identified and suggestions for improvement are proposed. The information in this report provides a framework for planning improvements in the delivery of services in Wikwemikong. The report also provides information on lessons learned and best practices for other First Nations communities planning to implement full delivery of the Ontario Works program.